HUBUNGAN ANTARA LINGKUNGAN KERJA DAN KOMPENSASI DENGAN TURNOVER INTENTION PADA KARYAWAN COFEESHOP DI KOTA KUDUS - Indah, Mega Indah Fakhrunnisa; Nugraini Aprilia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The purpose of this study was to empirically determine the relationship between work environment and compensation with turnover in coffeeshop employees in Kudus city. This research is quantitative in nature. This research was conducted at Jota Kudusi from September to December 2024. In this study, researchers took the population as active employees for 2 years at the coffeshop who had been affected by turnover. The sampling technique used in this study is non probability sampling with purposive sampling method. Collecting data in this study using the work environment scale, compensation scale, and turnover scale. Data analysis in this study used two predictor regression analysis methods and product moment. The results of this study indicate that the major hypothesis which says there is a significant relationship between work environment and compensation with turnover is accepted with an effective contribution of 25.1%. Thus, the conclusion of this study is that work environment and compensation have a significant influence on turnover in coffeeshop employees in Kudus City.